Effects of drying temperature on the sourness of dehydrated libas (Spondias pinnata) leaves - Damaso, Catherine Hofileña
This study was aimed to establish a method aimed at the preservation of the sour libas Spondias pinnata) leaves, in order to promote further utilization and cultivation.